Beauveria bassiana untuk Pengendalian Bemisisa tabaci pada Budidaya Kedelai Organik - Iqbal Erdiansyah; Suwardi Suwardi; Geby Wulandari (Agrotechnology Research Journal, 2023)
The whitefly (Bemisia tabaci) pest is one of the obstacles in soybean cultivation; it can reduce yields by up to 80%, even resulting in crop failure if not controlled. The purpose of this study was to determine the efficacy of the bioinsecticide Beauveria bassiana on whitefly death and the effect of B. bassiana and soursop leaf pesticides on pests, growth, and production in organic soybeans. The design used was non-factorial RAL with six treatment levels and four replications to determine the value of mortality and a comparison method between the treatments of B. bassiana and soursop leaf pesticide. The effective concentration of B. bassiana against whiteflies was 10%, with 85% mortality. The application of B. bassiana and soursop leaf pesticides showed no significant effect in suppressing attack and pest populations but also had no significant effect in increasing the growth and production of soybean plants on the observation variables of plant height, number of pods per sample, weight of 100 seeds, and total production, and the use of B. bassiana is not harmful to the survival of beneficial predators. The effective concentration of B. bassiana against whiteflies is 10%, with 85% mortality. The results of a comparison of B. bassiana with soursop leaf pesticides showed results that showed no different effect on all variables of pests as well as soybean growth and production. B. bassiana has potential as a biological agent for pest control because it is relatively safe against non-target insects such as natural enemies and beneficial arthropods.